1967
DOI: 10.1038/216936a0
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside Synthesis under Potentially Prebiotic Conditions

Abstract: DNA synthesis after treatment with cortisol is not the result of a direct interference with a biosynthetic pathway, but is simply a res1<1lt of the reduction in the number of cells able to incorporate thymidine. Other effects of cortisol on lymphatic tissue, such as decreased glucose utilization and decreased protein synthesis, als@ may be U10 result of this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Experimentally, Oró demonstrated a plausible prebiotic synthesis of deoxyribose starting with simple aldehydes but in about 3 % yield [9] . The synthesis of deoxyadenosine (7 % yield) was reported by Ponnamperuma starting from adenine and 2‐deoxyribose [10] . Sutherland in 2014, [11] and later Clarke in 2017, [12] showed the synthesis of deoxyribose under prebiotic conditions.…”
Section: Introductionmentioning
confidence: 89%
“…Experimentally, Oró demonstrated a plausible prebiotic synthesis of deoxyribose starting with simple aldehydes but in about 3 % yield [9] . The synthesis of deoxyadenosine (7 % yield) was reported by Ponnamperuma starting from adenine and 2‐deoxyribose [10] . Sutherland in 2014, [11] and later Clarke in 2017, [12] showed the synthesis of deoxyribose under prebiotic conditions.…”
Section: Introductionmentioning
confidence: 89%
“…21 Their composition reveals that formamide, together with cyanhydric acid (HCN), isocyanate (HNCO) and water (H 2 O), constitutes the most abundant molecules containing the four biologically relevant elements, O, N, H and C. [22][23][24] Hence, formamide seems to play a positive role as a synthon for purine and pyrimidine nucleobases acting as a prebiotic precursor. [25][26][27][28] The efficiency of formamide chemistry in the origin of the informational polymers strictly depends on the metal oxides and minerals used in its condensation. 29 The reactivity of this molecule has also attracted much attention because it constitutes a suitable model to study the reactivity of larger biochemical compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous solutions of carbohydrates are reported to be unstable [38]. Reid and Orgel observed that diluted solutions of carbohydrates under prebiotic conditions degrade within hours or days [60] and ribose decomposes even at low temperature and neutral pH (44 years at 0< T ≤ 150 • C) [42]. None of the experiments contain, however, any information about the quality of the water, used for the solutions.…”
Section: Carbohydratesmentioning
confidence: 99%